2011
DOI: 10.4314/ajid.v5i2.66514
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology of lymphatic filariasis and community practices and preceptions amongst the Ado People of Benue State, Nigeria

Abstract: As part of efforts to initiate lymphatic filariasis elimination activities in Benue State, this study employed the use of lymphatic filariasis-related clinical signs as rapid diagnostic features, immunochromatographic card test (ICT) to detect circulating filarial antigen (CFA) and questionnaire to investigate community perceptions and beliefs. 81 (32.6%) out of the 248 persons were positive for circulating filarial antigen (CFA). Infection rates denoted by CFA ranged from 41 (46.1%) in Uffia to 1(6.6%) in Iji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…This included reasons such as eating contaminated food, sexual intercourse, or dirty environment, rather than to the actual cause which is filarial worms in mosquito bites. Our findings on misconception about causes of LF corroborates findings from a previous study carried out in Benue state, Nigeria where majority in the study reported causes of LF as lack of personal hygiene, walking long distances, stepping on charm (13).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This included reasons such as eating contaminated food, sexual intercourse, or dirty environment, rather than to the actual cause which is filarial worms in mosquito bites. Our findings on misconception about causes of LF corroborates findings from a previous study carried out in Benue state, Nigeria where majority in the study reported causes of LF as lack of personal hygiene, walking long distances, stepping on charm (13).…”
Section: Discussionsupporting
confidence: 90%
“…Table 1 shows the socio-demographic profile of the respondents. Nigeria where majority in the study reported causes of LF as lack of personal hygiene, walking long distances, stepping on charm (13).…”
Section: Sociodemographic Characteristics Of Respondentsmentioning
confidence: 96%
“…This study on research question one identified 12 indicators that described the appropriateness of the assessed manual for evaluating ready-to-wear apparels produced which include: originality of the manual, simplicity in the use of the manual for evaluating ready-to-wear apparels, comprehensiveness of the contents of the manual, suitability of the objectives of the manual, achievement of the objectives, assessed step-by-step procedure for evaluating ready-to-wear apparels, users friendliness of the manual, overall relevance of the manual to clothing and textile industry, appropriateness of the identified areas to evaluate in the apparels using the manual, identification of the construction details in the apparel using the developed manual, suitability of the guidelines for judging quality of the apparel and appropriateness of operational measurement of the manual. The findings of this study conformed to the report of the study of Agbo (2013) that the appropriateness of the garment for physically challenged on the different sizes is determined by testing for: fit, comfort, ease of mobility, acceptability. The findings of this study also supported that of Stamper (2005) who identified the indicators of appropriateness of an operational manual to include originality, simplicity in the use of the manual, suitability of the objectives of the manual, user's friendliness of the manual, appropriateness of the manual and suitability of the guidelines.…”
Section: Discussion Of Findings Appropriateness Of the Manual Assesse...supporting
confidence: 83%
“…Lymphatic filariasis in North Central and North East, Nigeria: a high endemicity (32.60%) of CFA prevalence through ICT with 8.50% hydrocele, 6.40% lymphedema, and subjects´ need for awareness of the disease was reported in Ado LGA of Benue State [ 37 ]. Although Kogi State is reported with the highest number of people living with NTDs in Africa, 3.40% microfilaria prevalence from blood samples collected at night (between 9.00 PM-12.00 AM) with dermatitis (3.70%), hydrocele (0.70%), elephantiasis (3.70%), and hosts´ exposure to vectors were reported among 5 communities in Yagba West LGA of the State [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%